MENINGKATKAN PEMAHAMAN KONSEP MATEMATIKA MELALUI PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) - Bunga Isra Anngraeni (Departemen Matematika, 2020)
Understanding the concept is a basic ability that must be possesed by every student. In fact understanding mathematic concept of at grade VII in SMPN 34 Padang still low. This can be seen the first ability test results show the students haven’t been able to solve the problems givem to each indicator. One of the efforts to overcome this problem is to apply the CTL approach. The type of this research is study literature sourced from journals, scientific articles related with understanding mathematic concept and CTL approach. Based on the analysis of journals, it was found that there was an increase in the activity and understanding mathematic concept after the implementation of the CTL approach and each indicator on understanding mathematic concept can be improve through the principles of CTL. So it can ve conclution that CTL approach has a tendency to improve understanding mathematic concept of students. Keywords—Contextual Teaching and Learning approach, Study literature, Understanding of mathematical concepts